Pengaruh Pelatihan Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan PT Karisma Bahana Gemilang Jakarta - Syahputra Pasaribu, Andy; Lestari, Tri (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
PT Karisma Bahana Gemilang, a retail company located in West Jakarta, is the subject of this study. This study aims to learn how work motivation and job training partially and simultaneously impact on the performance of PT Karisma Bahana Gemilang workers. This study looked at 58 employees of PT Karisma Bahana Gemilang. The saturated sample method, which involves all members of the population, was used to select the nonprobability sample, which resulted in 58 samples. Quantitative statistical methods were used to analyze the data, and the IBM SPSS Statistics V.20 program was used. The results showed that job training (X1) partially affects employee performance (Y). The work motivation variable (X2) also significantly affects. With a coefficient of determination of 0.475, job training (X1) and work motivation (X2) have a positive and significant effect on employee performance (Y). Overall, job training (X1) and work motivation (X2) have a positive and significant influence on employee performance by 47.5%. Other variables not examined in this study have an influence of 52.5%.